Characteristics of Pie Crusts Made from Modified Cassava Flour (MOCAF) and Red Bean Flour - Siregar, Erpiani; Ayu, Dewi Fortuna; Putri Elvis, Shelby Julia; Diana, Ayu; Rahmayuni, Rahmayuni (Journal of Food and Pharmaceutical Sciences, 2026)
The development of bakery products has increased the demand for wheat flour alternatives, especially for individuals with dietary restrictions. This study aims to investigate the characteristics of pie crusts made from MOCAF (modified cassava flour) and red bean flour at various ratios. The experimental method used was a completely randomized design (CRD) with four treatments: MK1 (90% MOCAF, 10% red bean flour), MK2 (85% MOCAF, 15% red bean flour), MK3 (80% MOCAF, 20% red bean flour), and MK4 (75% MOCAF, 25% red bean flour). The parameters evaluated included moisture content, ash content, protein content, fat content, and sensory testing (color, aroma, taste, and crumb texture) using descriptive and hedonic tests. The results of the study showed that increasing the proportion of red bean flour significantly affected the sensory characteristics and nutritional content of pie crusts. MK4, with a ratio of 75% MOCAF and 25% red bean flour, achieved the highest hedonic scores for color (3.63), taste (3.50), aroma (3.86), and crumbly texture (4.18), which were most preferred by the panelists. Proximate analysis revealed that MK4 had a moisture content of 4.21%, ash content of 1.88%, protein content of 9.94%, and fat content of 26.09%. In conclusion, the addition of red bean flour to the pie crust formulation with MOCAF improves sensory quality and nutritional value, making it a suitable alternative for healthier bread products.